An experimental study on flexural strength enhancement of concrete by means of small steel fibers (Fracture and Structural Integrity, 2013)
Cost effective improvement of the mechanical performances of structural materials is an important goal in construction industry. To improve the flexural strength of plain concrete so as to reduce construction costs, the addition of fibers to the concrete mixture can be adopted. The addition of small steel fibers with different lengths and proportion have experimentally been analyzed in terms of concrete flexural strength enhancement. The main objectives of the present study are related to the evaluation of the influence of steelfibers design on the increase of concrete flexural characteristics and on the mode of failure. Two types of beams have been investigated. The force level, deflection and time to failure of beams have been measured. The shear crack, flexural crack and intermediate shear-flexural crack have been studied. The steel fiber content controlled crack morphology. Flexural strength and time to failure of fiber reinforce concrete could be further enhanced if, instead of smooth steel fibers, corrugated fibers were used.
Keywords: Steel fiber